Patients with chronic kidney disease have abnormal upper gastro‐intestinal tract digestive function: A study of uremic enteropathy. Issue 2 (February 2017) - Grant, Claire J; Harrison, Laura E; Hoad, Caroline L; Marciani, Luca; Gowland, Penny A; McIntyre, Christopher W
Abstract: Background and Aim: Chronic kidney disease (CKD) affects gastrointestinal (GI) function and results in numerous adaptive and maladaptive responses. Disruption of the colonic microbiome and its attendant consequences—the loss of gut barrier integrity and increased generation of uremic toxins—has become well‐recognized. However, less attention has been paid to characterizing the mechanisms behind dysfunction of the upper GI tract, largely owing to the difficulty of studying small bowel function in vivo . This present study was designed to comprehensively describe upper GI function in those with advanced renal impairment. Methods: Thirty‐five non‐diabetic subjects (12 CKD stage 4/5 patients, 23 healthy controls) underwent detailed GI magnetic resonance imaging (MRI) in both fasted and fed states. Upper GI function was assessed by quantification of gastric emptying and intra‐luminal small bowel water. Characterization of hydration and cardiovascular status was performed at baseline. Gut barrier integrity was assessed using serum endotoxin level. Results: Chronic kidney disease was associated with dysmotility (gastric half‐emptying time 96 ± 32 vs 74 ± 27 min, P  = 0.04) and reduced fasting and post‐prandial small bowel water (36 ± 22 mL vs 78 ± 42 mL, P  < 0.001), reflecting abnormal digestive secretion, and absorption. This was related to the degree of endotoxemia ( r  = −0.60, P  = 0.04) and poorer symptom scores, but not to disease severity, arterial stiffness or hydration status. Conclusion: Chronic kidney disease adversely affects digestive function. Abnormalities in digestive secretion and absorption may potentially have a broad impact in the prevention and treatment of both CKD and its complications. Further study is required to assess the factors that contribute to this dysfunction in a wider CKD population.